Digital Media and Islamic Matchmaking in Indonesia: The Case of “Kelas Jodoh” - Lina Kamila; Yessika Nurmasari; Acep Muslim (Medya ve Din Araştırmaları Dergisi)
The increase of religiosity in Indonesia, which has coincided with the development of digital media, has led to the emergence of various services that incorporate religious values, including in the areas of education and the facilitation of the marriage process. This study examines “Kelas Jodoh” (KJ) or “Matchmaking Class” as a case study to understand the role of digital media-supported Islamic matchmaking organizers within the context of existing Islamic matchmaking practices in Indonesia, particularly against the backdrop of rising personal piety and the use of digital media. It investigates how Islamic values governing pre-marital male-female relationships interact with the technological affordances of digital media, contributing to the evolution of digital religion. The study applies a qualitative case study method, with data collected through interviews with the KJ owner and manager, as well as with members (KJ’s participants). The findings indicate that KJ represents a fusion of increasing Islamic piety among urban Muslims and the growth of digital media, thus continuing to shape and expand the horizon of digital religion. The study also demonstrates how KJ’s use of digital tools and its mediator role reflect practices akin to those of modern Islamic movements such as the Tarbiyah group.